7 oktyabrya : den' konstitutsii SSSR - Gordon, M (Плакат СССР (Plakat), 1984)
Illustration of Soviet flag flying over photographs of cheering crowds Original title: 7 oктября : день конституции СССР Suggested translation: 7 October : Constitution day of the USSR PO-0890